In Vitro Bone Cell Models: Impact of Fluid Shear Stress on Bone Formation - Wittkowske, Claudia; Reilly, Gwendolen C.; Lacroix, Damien; Perrault, Cecile M. (Frontiers in Bioengineering and Biotechnology, 2016)
This review describes the role of bone cells and their surrounding matrix in maintaining bone strength through the process of bone remodelling. Subsequently, this work focusses on how bone formation is guided by mechanical forces and fluid shear stress in particular. It has been demonstrated that mechanical stimulation is an important regulator of bone metabolism. Shear stress generated by interstitial fluid flow in the lacunar-canalicular network influences maintenance and healing of bone tissue. Fluid flow is primarily caused by compressive loading of bone as a result of physical activity. Changes in loading, e.g. due to extended periods of bed rest or microgravity in space are associated with altered bone remodelling and formation in vivo. In vitro, it has been reported that bone cells respond to fluid shear stress by releasing osteogenic signalling factors such as nitric oxide and prostaglandins. This work focusses on the application of in vitro models to study the effects of fluid flow on bone cell signalling, collagen deposition and matrix mineralization. Particular attention is given to in vitro set-ups which allow long-term cell culture and the application of low fluid shear stress. In addition, this review explores what mechanisms influence the orientation of collagen fibres which determine the anisotropic properties of bone. A better understanding of these mechanisms could facilitate the design of improved tissue-engineered bone implants or more effective bone disease models.